NLRP3 inflammasome suppression improves longevity and prevents cardiac aging in male mice. Issue 1 (18th October 2019) - Marín‐Aguilar, Fabiola; Lechuga‐Vieco, Ana V.; Alcocer‐Gómez, Elísabet; Castejón‐Vega, Beatriz; Lucas, Javier; Garrido, Carlos; Peralta‐Garcia, Alejandro; Pérez‐Pulido, Antonio J.; Varela‐López, Alfonso; Quiles, José L.; Ryffel, Bernhard; Flores, Ignacio; et al.
Abstract: While NLRP3‐inflammasome has been implicated in cardiovascular diseases, its role in physiological cardiac aging is largely unknown. During aging, many alterations occur in the organism, which are associated with progressive impairment of metabolic pathways related to insulin resistance, autophagy dysfunction, and inflammation. Here, we investigated the molecular mechanisms through which NLRP3 inhibition may attenuate cardiac aging. Ablation of NLRP3‐inflammasome protected mice from age‐related increased insulin sensitivity, reduced IGF‐1 and leptin/adiponectin ratio levels, and reduced cardiac damage with protection of the prolongation of the age‐dependent PR interval, which is associated with atrial fibrillation by cardiovascular aging and reduced telomere shortening. Furthermore, old NLRP3 KO mice showed an inhibition of the PI3K/AKT/mTOR pathway and autophagy improvement, compared with old wild mice and preserved Nampt‐mediated NAD + levels with increased SIRT1 protein expression. These findings suggest that suppression of NLRP3 prevented many age‐associated changes in the heart, preserved cardiac function of aged mice and increased lifespan. Abstract : In this study, we have shown the potential role of the NLRP3 inhibition to modulate several anti‐aging mechanisms during cardiac aging. This work highlights the importance of examining the therapeutic and prophylatic value of small molecule inhibitors of NLRP3 and its effects as potential therapy for preventing cardiac and metabolic aging.